The strategy of professional football clubs in utilizing sports facilities to activate sources of self-financing: A field study of first division professional clubs. - Bouslah, Nadhir (sports creativity, 2025)
This study aimed to identify the strategies employed by professional football clubs in utilizing sports facilities to generate self-financing. The study was conducted on a sample of eight club presidents from the top-tier professional football league. This sample was randomly selected to allow for generalization of the results to the wider population. The descriptive methodology, deemed most suitable for this type of study, was employed, utilizing a questionnaire administered to the presidents of the professional clubs. The results indicated that the presidents of these clubs follow a well-structured strategy for leveraging sports facilities as a source of funding. This strategy involves investing in the facilities themselves, marketing services, and securing sponsorships. Given the demands of professionalism as a dominant system in the sports field, where self-financing plays a crucial role in addressing the challenges faced by professional clubs, it has become imperative for these clubs to utilize their sports facilities as a primary source of self-financing.